ANALISIS HUBUNGAN FAKTOR GENETIK DENGAN KEJADIAN HIPERTENSI PADA USIA DEWASA MUDA (19-49 TAHUN) DI PUSKESMAS BAKUNASE KOTA KUPANG TAHUN 2020 - Stefania Jawa Ina; Jannes Bastian Selly; Fepyani Tresna Feoh (Citra Bangsa University - Literacy and Publishing Center (CBU-LPC), 2020)
ABSTRACT Hypertension or high blood pressure is the cause of death and high illness. Hypertension as a chronic disease is influenced by several factors. The risk factors for hypertension are divided into non-modifiable risk factors and modifiable risk factors. The purpose of this study was to determine the relationship between genetic factors and the incidence of hypertension in the young adult age group (19-49 years) at Bakunase Health Center, Kupang City. This research is a quantitative study with a correlational design and cross sectional approach. The sample size was 116 people with purposive sampling technique. The results of the study using the Spearman rho statistical test showed that there was a relationship between genetic factors (p Value = 0.000) and the incidence of hypertension in young adults (19-49 years) at Bakunase Health Center, Kupang City.